Anticlericalismo y herejía : el problema conceptual - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Historia Antigua, Medieval y Moderna. Actas y comunicaciones del Instituto de Historia Antigua y Medieval, 2016)
Este artículo se cuestiona la idea que en León y Castilla no hubo herejías durante la Edad Media. En realidad hubo movimientos sociales muy cercanos a la herejía. Las rebeliones de los burgueses de Sahagún y Santiago de Compostela, de principios del siglo XII, contra el abad y el obispo, tuvieron las características esenciales de los movimientos heréticos del período, aunque no fueron calificados como tales por la jerarquía de la iglesia.

This article challenges the idea that there were no heresies in Leon and Castilla during the Middle Ages. In reality there were social movements very close to heresy. The rebellions of the bourgeois of Sahagun and Santiago de Compostela, in the early twelfth century, against the abbot and bishop, had the essential characteristics of the heretical movements of the period, although they were not qualified in this way by the church hierarchy.
Anticlericalism and heresy : the conceptual problem
This article challenges the idea that there were no heresies in Leon and Castilla during the Middle Ages. In reality there were social movements very close to heresy. The rebellions of the bourgeois of Sahagun and Santiago de Compostela, in the early twelfth century, against the abbot and bishop, had the essential characteristics of the heretical movements of the period, although they were not qualified in this way by the church hierarchy.
Fil: Astarita, Carlos. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina.
Fil: Astarita, Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.
Keywords: LÉON Y CASTILLA; MOVIMIENTOS ANTICLERICALES; EDAD MEDIA; HEREJÍAS; LEON AND CASTILLA; ANTICLERICAL MOVEMENTS; MIDDLE AGES; HERESIS